The role of rotating hinge implants in revision total knee arthroplasty. Issue 6 (June 2019) - Pasquier, Gilles; Ehlinger, Matthieu; Mainard, Didier
Abstract : Hinged implants are the most constrained knee replacement prostheses. They are very useful in complex cases of total knee arthroplasty (TKA) revision. Hinged implants have evolved with rotating bearings and modularity that allows local joint reconstruction or segmental bone replacement. They are required when significant instability persists in cases with inadequate collateral ligaments and significant flexion laxity. They are now used when a large bone defect is reconstructed, or when bone fixation of the implant is questionable especially in the metaphyseal zone. The use of hinged implants in TKA revision is associated with high complication rates. Published outcomes differ based on the patients' aetiology. The outcomes of rotating-hinged implants used in septic revisions or salvage situations are poorer than other types of revision and have a higher complication rate. The poor general health of these patients is often a limitation. Despite these relatively poor results, hinged implants continue to have a place in revision surgery to solve major instability or to obtain stable bone fixation of an implant when the metaphysis is filled with bone grafts or porous devices. Cite this article: EFORT Open Rev 2019;4 DOI: 10.1302/2058-5241.4.180070